Vascular Malformations of the Central Nervous System - Gürer, Bora; Kuru Bektaşoğlu, Pinar (IntechOpen, 2020)
Vascular malformations of the central nervous system are important pathologies that could present with abrupt onset hemorrhage resulting in devastating neurological deficits. Current knowledge of their biology and natural history is increasing. Diagnostic modalities help clinicians to better evaluate the individual cases, and to decide the best treatment options. Treatment alternatives are various and all treatment options should be evaluated before choosing the final therapeutic modality. The purpose of this book is to review the current knowledge about vascular malformations of the central nervous system and to evaluate the treatment alternatives.